2007
DOI: 10.3171/jns-07/08/0347
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of cerebrospinal fluid rhinorrhea after vestibular schwannoma surgery by reconstruction of the drilled porus acusticus with hydroxyapatite bone cement

Abstract: The use of HAC in the reconstruction of the drilled posterior wall of the porus acusticus, occluding exposed air cells, greatly reduces the risk of CSF rhinorrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 19 publications
2
28
1
Order By: Relevance
“…Perimeatal cells may communicate with air cell tracts in the petrous apex, peritubal region, perilabyrinthine region, or retrofacial region. A CSF leak rate of 6.6% was identified in this current series, which was comparable to published rates with the standard retrosigmoid approach of 6% to 18.7% 8–12. Careful obliteration of air cells in the region of the IAC drill‐out is essential to eliminate potential routes for postoperative CSF leak.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Perimeatal cells may communicate with air cell tracts in the petrous apex, peritubal region, perilabyrinthine region, or retrofacial region. A CSF leak rate of 6.6% was identified in this current series, which was comparable to published rates with the standard retrosigmoid approach of 6% to 18.7% 8–12. Careful obliteration of air cells in the region of the IAC drill‐out is essential to eliminate potential routes for postoperative CSF leak.…”
Section: Discussionsupporting
confidence: 74%
“…Additionally, within this series no patients experienced meningitis following the modified retrosigmoid approach. This is lower than previous reports in the literature of 1.5% to 3.7% for all approaches and approximately 3.8% to 7.3% for the retrosigmoid approach specifically 12, 14, 16…”
Section: Discussioncontrasting
confidence: 73%
“…Baird and colleagues have described a limited method of HAC use wherein cement is placed only around the drilled posterior wall of the porus acusticus, creating a significant reduction of their CSF leak rate from 12 to 2.3%. 20 We propose that the addition of titanium mesh to the closure limits the amount of HAC that must be used in replacing the bony defect caused by the mastoidectomy. In addition, we have found that the introduction of medial bowing to the mesh once it is secured to the cortex provides uniform and permanent pressure to the fat graft, allowing for a more effective seal of air-cell tracts than standard fat application techniques and potentially contributing to the lack of not only CSF leakage but also the incidence of subgaleal CSF effusions.…”
Section: Discussionmentioning
confidence: 99%
“…[1910111726] While some authors have demonstrated HBC as an acceptable method of preventing CSF leaks in craniotomies of the skull base,[171112] others have used the cement as an adjunct to titanium mesh, plates, fat grafts, and/or dural substitutes. [218]…”
Section: Introductionmentioning
confidence: 99%